Quantitative dysmorphology assessment in Fabry disease - Ries, Markus; Moore, David F.; Robinson, Chevalia J.; Tifft, Cynthia J.; Rosenbaum, Kenneth N.; Brady, Roscoe Owen; Schiffmann, Raphael; Krasnewich, Donna (Genetics in medicine, 2006)
Purpose: 1) To identify morphometric characteristics in hemizygous patients with Fabry disease a treatable lysosomal storage disorder caused by the deficiency of α-galactosidase A where morphological abnormalities have occasionally been mentioned, but have never been investigated systematically. 2) To devise a quantitative method to evaluate dysmorphic abnormalities in Fabry disease. Method: Cross-sectional, single center, independent dysmorphology assessment by a panel of three clinical geneticists, based on standardized medical photography. Population: consecutive hemizygous patients with Fabry disease (N = 38) unselected for the features assessed, mean age 38 ± 10.8 years (range: 10-60), recruited for neuropathic pain into enzyme replacement therapy trials. Results: The following dysmorphic features were identified (in order of descending frequency): periorbital fullness, prominent lobules of the ears, bushy eyebrows, recessed forehead, pronounced nasal angle, generous nose/bulbous nasal tip, prominent supraorbital ridges, shallow midface, full lips, prominent nasal bridge, broad alar base, coarse features, posteriorly rotated ears, and prognathism. Extremity features included broad fingertips, short fingers, prominent superficial vessels of hands, 5th digit brachydactyly, and 5th digit clinodactyly. Narrow anterior-posterior chest diameter was noted. Ten core features were statistically defined. Cronbach's alpha measuring internal consitency was 0.62. Light's kappa for global inter-rater variability was 0.26 while Cohen's kappa allowing pair-wise rater comparison varied between 0.08-0.48. Conclusions: Patients with Fabry disease share common morphological characteristics of the face, trunk, and extremities. Some of these features are subtle as documented by the inter-rater variability. Awareness of these features may facilitate the diagnosis of patients with Fabry disease, and identification of affected family members.